The Processes of Energy Transformation in Activated Laser Materials with Ions Er3 (Review) - Kevshyn, A.H.; Halyan, V. V.; Semenyuk, T. A. (Physics and Chemistry of Solid State, 2015)
In paper the features of energy transformation processes in activated with erbium ions laser materials based on optical transitions in 4f shell of Er3+ ionwere discussed. Methods of excitation of the luminescence in chalcogenide glasses doped with Er3+ ions were described and found how its intensity depends on concentration of the ions. Up-conversion and cross-relaxation play an important role in the transformation of excitations in erbium-doped materials. In cross-relaxation the energy of one center can be nonradiatively transferred to another center or divided between the two centers, while in the up-conversion, however, energy of several centers summed up in one center, bringing it acts as an additional channel of luminescence quenching, or as a way of pumping of the higher energy levels. To improve the efficiency of optical excitation of many laser materials doped with erbium ions the sensitization with ytterbium ions that have intense absorption band in the range of 0.9-1 µm with "effective" width of about 1000 cm-1 as well a channel of the efficient nonradiative excitation energy transfer to Er3+ ions is widely used.